Dynamics of Progesterone, TNF-α, and a Metabolite of PGF2α in Blood Plasma of Beef Cows following Embryo Transfer. (2nd October 2014) - Mason, M. C.; Copeland, J.; Cuadra, E. J.; Elsasser, T. H.; Jung, Y.; Larson, J.
Abstract : Lactating beef cows previously synchronized for estrus (d 0) were assigned to four treatments to assess their effectiveness in increasing blood progesterone (P4) and its effects on tumor necrosis factor-α (TNF-α) and prostaglandin F2α (PGF2α) after the transfer of embryos. At the time of transfer (d 7), cows received no treatment (control; n = 16 ), a controlled internal drug releasing device (CIDR; n = 16 ), human chorionic gonadotropin (hCG; n = 15 ), or gonadotropin releasing hormone (GnRH; n = 15 ). Blood samples were taken on d 7, 14, and 21 for analysis of P4 and tumor necrosis factor-α (TNF-α). Blood was collected (every 15 min for 2 h) in half the animals in each treatment group on d 14 and the remaining half on d 21 for analysis of prostaglandin F2α metabolite (PGFM). Retention rates were 56.2, 62.5, 46.7, and 13.3% for cows in the control, CIDR, hCG, and GnRH groups, respectively. Progesterone was greater (P ≤ 0.05 ) in cows receiving hCG compared to others on d 14. Progesterone in all treatment groups increased from d 7 to d 14 and declined (P ≤ 0.05 ) from d 14 to d 21. Contrary to pregnant cows, P4 and TNF-α declined from d 7 to d 21 in nonpregnant cows (P ≤ 0.05 ). Although PGFM increased by d 21, there was no difference between pregnant and nonpregnant cows.